2014
DOI: 10.1002/14651858.cd010870.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Surgical treatment of stage IA2 cervical cancer

Abstract: We found no evidence to inform decisions about different surgical techniques in women with stage IA2 cervical cancer. In the future, the results of one large ongoing RCT should allow comparison of different types of surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 42 publications
0
22
0
1
Order By: Relevance
“…2 In the field of fertility preservation for early-stage cervical cancer (which is well documented and widely performed), even if comparative retrospective studies were published, there would be no strong evidence that any form of surgical technique is better, equal, or worse in prolonging survival. 29 Ovarian preservation seems to be safe in patients with grade 2 or 3 EC confined to the endometrium. On the contrary, the results of this study show that uterine preservation increases the risk of mortality; therefore, careful and timelimited fertility-sparing management in patients with grade 2 or 3 EC is warranted.…”
Section: Discussionmentioning
confidence: 98%
“…2 In the field of fertility preservation for early-stage cervical cancer (which is well documented and widely performed), even if comparative retrospective studies were published, there would be no strong evidence that any form of surgical technique is better, equal, or worse in prolonging survival. 29 Ovarian preservation seems to be safe in patients with grade 2 or 3 EC confined to the endometrium. On the contrary, the results of this study show that uterine preservation increases the risk of mortality; therefore, careful and timelimited fertility-sparing management in patients with grade 2 or 3 EC is warranted.…”
Section: Discussionmentioning
confidence: 98%
“…Cervical cancer, commonly induced by chronic infection of human papillomaviruses (HPV), is the major cause of death in gynecological cancers and accounts for almost 12 % of all cancers among women worldwide [1][2][3]. Squamous cell carcinoma (SCC) represents the predominant subtype of cervical cancer [4].…”
Section: Introductionmentioning
confidence: 99%
“…Multiple reviews and retrospective studies offer widespread agreement that for selected cervical tumours (<2 cm in size, with no lymphovascular space invasion) there is low risk (0.6–3%) of parametrial involvement, with SVT offering a potentially equivalent oncological outcome 16–19. However, a Cochrane review by Kokka et al 20 suggested that no conclusions regarding effectiveness and safety could be confidently reached due to the absence of randomised trials. In the context of carefully assessed cervical premalignancy where parametrial and vaginal margins are not relevant, the authors would extrapolate that SVT represents a safe alternative to simple hysterectomy, in the same way that RVT offers a safe alternative to radical hysterectomy for small 1b1 cervical tumours.…”
Section: Discussionmentioning
confidence: 99%